Writing good economics: How texts 'on the move' perform the lab and discipline of experimental economics. (June 2022) - Asdal, Kristin; Cointe, Béatrice
How is objectivity accomplished in laboratory economic experiments? To address this question, this paper focuses on a modest and mundane thing: the written instructions that guide experimental subjects in the lab. In a material-semiotic perspective, these instructions can be understood as text-devices. We follow text-devices 'on the move' from their very writing, through the lab, the review process and out into the journal article. To do so, we analyse 'text-author ensembles', which are journal articles together with practice-oriented interviews with their authors. We show that instructions act not simply as texts, but as experimental instruments that also perform the procedure of experimental economics. They draw together the procedural, material and rhetorical dimensions of experimental work in economics, and link the lab setting to collective validation procedures within the discipline of economics. To achieve this, experimental economists rely on qualitative writing skills refined in collective writing and reviewing practices. These text-devices 'on the move' alert us not only to the role of writing and writing skills in the production of scientific knowledge, but to the role of texts as material and semiotic objects that can produce facts as well as labs and disciplines, and that are key to the accomplishment of objectivity in experimental economics.